2023
DOI: 10.1371/journal.pntd.0011356
|View full text |Cite
|
Sign up to set email alerts
|

An economic evaluation of Wolbachia deployments for dengue control in Vietnam

Abstract: Introduction Dengue is a major public health challenge and a growing problem due to climate change. The release of Aedes aegypti mosquitoes infected with the intracellular bacterium Wolbachia is a novel form of vector control against dengue. However, there remains a need to evaluate the benefits of such an intervention at a large scale. In this paper, we evaluate the potential economic impact and cost-effectiveness of scaled Wolbachia deployments as a form of dengue control in Vietnam–targeted at the highest b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Tantowijoyo, Tanamas ( Tantowijoyo et al., 2022 ) confirmed that introducing Wolbachia to reduce dengue had effective outcomes, as the mosquito population and insecticide resistance showed no significant differences between treated and untreated groups in the Applying Wolbachia to Eliminate Dengue trial. Turner, Quyen ( Turner et al., 2023 ) proposed that Wolbachia -infected mosquitoes to control dengue in high-risk urban areas of Vietnam is cost-effective, with a projected cost of $420 per health year saved. It was proposed that Releasing Wolbachia mosquitoes in ten high-burden cities that make up 40% of the country’s dengue cases, could prevent 6.2 million cases over 20 years, bringing significant health and economic benefits.…”
Section: Case Studies and Pilot Projectsmentioning
confidence: 99%
“…Tantowijoyo, Tanamas ( Tantowijoyo et al., 2022 ) confirmed that introducing Wolbachia to reduce dengue had effective outcomes, as the mosquito population and insecticide resistance showed no significant differences between treated and untreated groups in the Applying Wolbachia to Eliminate Dengue trial. Turner, Quyen ( Turner et al., 2023 ) proposed that Wolbachia -infected mosquitoes to control dengue in high-risk urban areas of Vietnam is cost-effective, with a projected cost of $420 per health year saved. It was proposed that Releasing Wolbachia mosquitoes in ten high-burden cities that make up 40% of the country’s dengue cases, could prevent 6.2 million cases over 20 years, bringing significant health and economic benefits.…”
Section: Case Studies and Pilot Projectsmentioning
confidence: 99%
“…[17] In Vietnam, another study found the technology similarly cost effective based on the 10-year time horizon, and cost-saving at the 20-year time horizon. [18] A simulation across seven Brazilian cities also found Wolbachia cost-effective across all 7 cities modeled, though not cost saving[19] in 2 of the 7 cities. In Suva, Fiji, a much smaller city, Wolbachia was acceptably cost-effective, but in Port Vila, Vanuatu, the relatively small target population and lower population density would not make the approach cost-effective there.…”
Section: Introductionmentioning
confidence: 99%